Development Of Performance Model For Quality And Process Improvement In Business Process Service Industry - Oluyinka, Oludapo Samson; Puteri Fadzline, Tamyez; Cheng, Jack Kie (EBSCO Industries, 2017)
When it comes to performance improvement process, literature abounds with lean, agile and lean-agile. Over the years, the implementation of the improvement processes of lean and agile had met with resounding success in the manufacturing, production, and construction industry. For this reason, there is an interest to develop a performance process for business process service industry incorporating the key aspect of lean and agile theory extracted from the extant literature. The researcher reviewed a total of 750 scholarly articles, grouped them according to the relationship to central theme - lean or agile, and thereafter uses factor analysis under principal component method to explain the relationship of the items. The result of this study showed that firms focusing on cost will minimize the investment of resources in business operations this, in turn, will lead to difficulties in responding to changing customer's requirements in terms of volume, delivery, and new product. The implication is that on the long run cost focus strategy negatively influence flexibility.